(untitled) (Asamblea. Revista parlamentaria de la Asamblea de Madrid, 2012)
This paper upholds the democratic importance of citizen participation at all stages of the legislative process. We analyze the constitutional and legal defi ciencies in this area and propose several policy reforms in order to, in the words of Hannah Arendt, approximate the communicative power and the creation of legitimate Law, thus recovering the promise of politics.